“Bathing in the Colour”: from the Ra Therapy to Contemporary Colour and Light Environment: (Polychromy as an eternal paradigm of the livable environment) - Zheleznyak, Olga (project baikal, 2019)
Studying the prospects of the colour phenomenon for the formation of the livable environment necessitates consideration of the integrity of the space of colour effect, including the biological colour behavior; intended Ra-therapy / chromotherapy; permanent polychromy of the environment constantly influencing the human organism; involvement of chromaticity in the ideas of livability of the environment and a healthy lifestyle; as well as the necessity of permanent monitoring in the constantly changing conditions of the reality.